2015
DOI: 10.5194/npgd-2-647-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Search for the 531 day-period wobble signal in the polar motion based on EEMD

Abstract: Abstract. In this study, we use a nonlinear and non-stationary time series analysis method, the ensemble empirical mode decomposition method (EEMD), to analyze the polar motion (PM) time series (EOP C04 series from 1962 to 2013) to find a 531 day-period wobble (531 dW) signal. The 531 dW signal has been found in the early PM seires (1962–1977) while cannot be found in the recent PM seires (1978–2013) using conventional analysis approaches. By the virtue of the demodulation feature of EEMD, the 531 dW can be co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Recently, Na et al (2011) found a 500-day period component in the PM data with an average amplitude of 20 mas, and argued that, if assuming the existence of this component, the RMS error of the prediction of the PM could be reduced by 50 %, and suggested that this phenomenon should be caused by resonance of an unidentified oscillating mode of the Earth (possibly the Earth's inner core wobble). In addition, this wobble (or referred to as an 18-month wobble) was found in the analysis of the atmospheric angular momentum data by Wahr (1983) and Chen et al (2010). Furthermore, a signal with a period of about 1.5 years could also be found from the variation of length of day (LOD) by using the wavelet analysis as suggested by Chao et al (2014).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Recently, Na et al (2011) found a 500-day period component in the PM data with an average amplitude of 20 mas, and argued that, if assuming the existence of this component, the RMS error of the prediction of the PM could be reduced by 50 %, and suggested that this phenomenon should be caused by resonance of an unidentified oscillating mode of the Earth (possibly the Earth's inner core wobble). In addition, this wobble (or referred to as an 18-month wobble) was found in the analysis of the atmospheric angular momentum data by Wahr (1983) and Chen et al (2010). Furthermore, a signal with a period of about 1.5 years could also be found from the variation of length of day (LOD) by using the wavelet analysis as suggested by Chao et al (2014).…”
Section: Introductionmentioning
confidence: 83%
“…Wahr (1983) implied that there exists an 18-month (∼ 547-day) polar wobble (which can be considered as coinciding with the 531 dW signal mentioned in the present paper), which could be caused by oceanic excitation. Chen et al (2010) further demonstrated that the atmospheric excitation may give rise to the 531 dW signal with an amplitude 15 mas using the atmospheric angular momentum (AAM) data set spanning from 1948 to 2006. But, from the above results, those excited 531 dW signals almost disappear from the 1978-1994 and 1995-2013 series.…”
Section: Results From the Pm Series With/without Using Eemdmentioning
confidence: 99%
See 3 more Smart Citations